CURRENT STATUS OF COMPARATIVE GENOMICS AND INHIBITORS OF PLASMODIUM SPECIES: A SYSTEMATIC REVIEW - MANOJ KUMAR YADAV; D SWATI; PK PATRA (International Journal of Pharma and Bio Sciences, 2016)
Malaria is still one of the most infectious and potentially lethal diseases known to mankind and typified by a series of intermittent fever episodes. This disease is responsible for high cases of mortality and morbidity in humans. The global incidence of malaria and its fatal consequences continue to be one of the worst catastrophes ever faced by mankind. P. falciparum, a parasitic protozoan, is responsible for a majority of malaria deaths. Another apicomplexan species, P. vivax, is the most widely distributed human malaria parasite infecting millions of individuals annually. Recently, P. knowlesi that normally infects long-tailed macaques also starts infecting humans. So, in-depth study of the pathogen is essential for combating the disease efficiently. Moreover, rise of drug-resistant cases in many areas, not only in developing countries but industrialized countries as well, during the past decade will make this situation more alarming. These situations, particularly the global resurgence of malaria and the rapid emergence of disease resistance, underscore the importance of the development of new antimalarial drugs. Achieving the goal of malaria-elimination will depend on the existing knowledge and available new information of disease. Unfortunately, malaria is a disease of poverty, and despite a wealth of scientific knowledge there is insufficient market incentive to generate the competitive antimalarial drug research and development that is normally needed to deliver new products. In this review, we tried to show the comparative genomics-based status of malaria causing different Plasmodium pathogens and, effectiveness of available antimalarial drugs.